2017
DOI: 10.3389/fendo.2017.00359
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Osteocyte-Ablation on Inorganic Phosphate Metabolism: Analysis of Bone–Kidney–Gut Axis

Abstract: In response to kidney damage, osteocytes increase the production of several hormones critically involved in mineral metabolism. Recent studies suggest that osteocyte function is altered very early in the course of chronic kidney disease. In the present study, to clarify the role of osteocytes and the canalicular network in mineral homeostasis, we performed four experiments. In Experiment 1, we investigated renal and intestinal Pi handling in osteocyte-less (OCL) model mice [transgenic mice with the dentin matr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…In fact, dietary Pi restriction up-regulates FGF15 expression in mouse ileum, but not in VDR-deficient mice (145). Conversely, high Pi-fed mice have significantly lower transcript levels of FGF15 in the ileum (146).…”
Section: Advance Article: Endocrine Reviewsmentioning
confidence: 93%
“…In fact, dietary Pi restriction up-regulates FGF15 expression in mouse ileum, but not in VDR-deficient mice (145). Conversely, high Pi-fed mice have significantly lower transcript levels of FGF15 in the ileum (146).…”
Section: Advance Article: Endocrine Reviewsmentioning
confidence: 93%
“…In 2013 Sato et al reported that the absence of osteocytes leads to lymphopenia and revealed that osteocytes are the important regulators of fat metabolism and lymphopoiesis [ 73 ]. It has been observed that in osteocyte-deficient mice, the absorption of inorganic phosphate (pi) increases in the intestine, which further stimulates the pi excretion from the renal system [ 74 ]. In addition, a study revealed that by expressing resistin, osteoclasts induce insulin resistance and suggest that suppression of osteoclasts generation could be a potential therapeutic strategy for insulin resistance [ 75 ].…”
Section: Bone Cells and Global Energy Metabolismmentioning
confidence: 99%
“…Although cathepsin K is mainly required for osteoclastic bone resorption, osteocytes also release cathepsin K and regulate mechanotransduction ( 70 ). Osteocytes release FGF23, dentin matrix acidic phosphoprotein 1 (DMP1), PHEX, and MEPE, and act as endocrine cells to regulate phosphate metabolism ( 1 , 71 73 ). Osteocytes release sclerostin to control bone mineralization via the modulation of DMP1, PHEX, MEPE, and FGF-23 expression ( 74 , 75 ).…”
Section: Introductionmentioning
confidence: 99%